Ceramic raw materials from the State of Maranhao, Brazil. Part 1: chemical and mineralogical characterization and technological properties of clays from Sao Luis, Rosario, Pinheiro and Mirinzal - Rivas Mercury, Jose Manuel; Correia, Gricirene Sousa; Lemos Silva Vasconcelos, Nazare Socorro [UNESP]; Cabral, Aluisio Alves; Angelica, Romulo Simoes (Escola de Minas, 2012)
This work involved the characterization of clays collected in the municipalities of Sao Luis, Rosario, Pinheiro and Mirinzal (state of Maranho, Brazil), based on specific mass, specific surface area, cation exchange capacity (CEC), particle size distribution, X-ray diffraction (XRD), differential thermal analysis (DTA), thermogravimetric analysis (TG-DTA) and Atterberg limits. Technological tests for ceramic applications were also carried out on compacts pressed under 20 MPa and heat-treated at 850, 950, 1050, 1150 and 1250 degrees C. Our results indicated that two of the clays composed of kaolinite, quartz, and anatase with high plasticity limits, have excellent properties and can be used in the whiteware industry. The other ones are red-firing clays and have a mineralogical composition of quartz, kaolin, feldspar, montmorillonite, hematite and goethite. The latter showed low and moderate values of plasticity, which makes them suitable for the production of heavy clay products.
Matérias-primas cerâmicas do Estado do Maranhão. Parte 1: caracterização químico-mineralógica e propriedades tecnológicas de argilas dos municípios de São Luís, Rosário, Pinheiro e Mirinzal
Keywords: Raw materials; Maranhao; Characterization